Dampak Penyunatan Takaran Minyak Goreng Kita terhadap Kepercayaan Masyarakat dan Upaya Perlindungan Konsumen: Studi Kasus PT. Artha Eka Global Asia - Sebastian Alboen Sihombing; Reva Setianingsih; God Godsent; Urai Vidia (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Legal protection for consumers is an important issue in maintaining public trust in products circulating in the market, especially in subsidized cooking oil products. Decreasing quality or cutting product content can affect consumer perception, which has an impact on decreasing trust in the product brand. This study aims to analyze the impact of legal protection on the consequences of cutting subsidized cooking oil and how this incident affects public trust. The research method used is a qualitative approach with a case study analysis of the event of cutting the contents of cooking oil products by PT AEGA. The results of the study indicate that non-compliance with product quality standards can cause consumer distrust and worsen the brand image that has been identified with the government subsidy program. Therefore, it is important for the government and business actors to increase transparency, supervision, and law enforcement so that the public does not feel disadvantaged and continues to trust the products they consume. This study also recommends strengthening regulations and legal counseling to the public to increase their awareness and participation in consumer protection.